Issues of Unity in Ovid's Tristia - Dettmer, Helena (Peter Lang Publishing, Incorporated, 2021)
Cover -- Table of Contents -- Chapter One: Introduction -- Background -- Manuscripts of the Tristia -- Ring-Composition Structure -- Consecutive-Ring Structure of Tristia 5.10 -- Ring-Composition Structure of Tristia 5.10 -- Ring Structures of Latin Poetry-Books -- Linear Structure of Poems within Poetry-Books and Run-On Poems -- Chapter Two: Tristia 1.5 and 1.9 -- Tristia 1.5a (1-44) -- Tristia 1.9a (1-36) -- Tristia 1.5a and 1.9a as Thematic Counterparts -- Tristia 1.8 -- Tristia 1.5b (45-84) -- Tristia 1.9b (37-66) -- Tristia 1.5b and 1.9b as Thematic Counterparts -- Ring-Composition Structure of Tristia Book 1 -- Chapter Three: Tristia 3.4 -- Tristia 3.4a (1-46) -- Tristia 3.4b (47-78) -- Tristia 3.4a and 3.4b as Consecutive Paired Poems -- Ring-Composition Structure of Tristia Book 3 -- Verbal and Thematic Parallels Common to Books 1 and 3 -- Chapter Four: Tristia 4.4 -- Tristia 4.4a (1-54) -- Tristia 4.4b (55-88) -- Identity of the Addressee of Tristia 4.5 -- Tristia 4.4a and 4.5 as Thematic Counterparts -- Metaphorical Interpretation of Tristia 4.4b -- Ring-Composition Structure of Tristia Book 4 -- Chapter Five: Tristia 5.2 and 5.7 -- Tristia 5.7a (1-24) -- Tristia 5.7b (25-68) -- Tristia 5.7b (25-42) -- Tristia 5.7b (43-64) -- Tristia 5.7b (25-42, 64-68) -- Tristia 5.7a and 5.7b as Consecutive Paired Poems -- Tristia 5.10 -- Tristia 5.7a, 5.7b, and 5.10 as Thematic Counterparts -- Tristia 5.2a (1-44) -- Tristia 5.2b (45-78) -- Tristia 5.2b and 5.11 as Thematic Counterparts -- Interlocking-Ring Structure of Tristia Book 5 -- Chapter Six: Conclusion -- Structural Analysis -- Ovid's Attitude toward Augustus -- Multiples of Five in Latin Poetry-Books -- Ovid's Ordering Principles of the Epistulae ex Ponto 1-3 -- Appendix A: Catullus 8 -- Appendix B: Text and Translation -- Index.